Pharmaceutical and Biotechnological Importance of Actinobacterial Products - Bhakyashree, Krishnamoorthy; Kannabiran, Krishnan (Indian Journal of Pharmaceutical Education and Research, 2020)
Many compounds produced by marine microbes possess significant pharmaceutical applications. Actinobacteria are one among the microbes producing a variety of antibiotics. Apart from antibiotics, it also produces many novel enzymes and important pharmaceutical products. Actinobacteria serves as a reservoir of antibiotics and novel chemical compounds and it contributes 80% of antibiotics available in the market. It was continuously been explored for novel bioactive compounds and new chemical entities. Many of them are more promising against microbial pathogens and even drug resistant pathogens. Apart from antibiotics, many enzymes are also produced by actinobacteria. The usage of enzymes in diverse pharmaceutical and biotechnological industries is gaining momentum and moreover, there is a growing demand for the discovery of novel metabolites and enzymes to fulfill the requirement of pharmaceutical industry. Apart from all these products actinobacteria also produces biosurfactants. Members of actinobactaerial genera have been extensively used in the removal of toxic dyes and other toxic pollutants. In this review, the up to date information available on the pharmaceutical and biotechnological uses of actinobacterial products and the scope for screening of actinobacterial genome for production of novel compounds for pharmaceutical applications have been discussed.
Keywords: Actinobacteria; Metabolites; Antibiotics; Enzymes; Biosurfactants; Dye; degradation